Penerapan Mind Mapping Berbantuan Google Classroom untuk Meningkatkan Hasil Belajar Siswa Kelas VII - Fika Rahmawati; Dyah Setyaningrum Winarni; Indri Nurwahidah (Indonesian Journal of Mathematics and Natural Science Education, 2020)
Abstrak Pola pengajaran yang konvensional di sekolah menjadikan siswa belum mampu menyerap konsep yang diajarkan, sehingga dibutuhkan model pembelajaran yang eksploratif dan menarik, seperti mind mapping. Pendekatan eksperimental pada kelas perlakuan dengan mind mapping dan kelas kontrol secara konvensional. Teknik pengumpulan data menggunakan instrumen tes untuk mengukur tingkat hasil belajar dan lembar observasi untuk mengukur penerapan mind mapping dalam proses pembelajaran. Hasilnya pembelajaran berjalan sesuai dengan prosedur pembelajaran. Hasil observasi pembelajaran terdapat 10 atau 36% siswa dalam kriteria sangat baik, 11 atau 39% dalam kriteria baik, 7 atau 25% dalam kriteria cukup baik dan tidak ada yang masuk kriteria kurang baik. Sedang pada observasi penugasan terdapat 8 atau 29% siswa dalam kriteria sangat baik, 13 atau 46% siswa dalam kriteria baik, 7 atau 25% siswa dalam kriteria cukup baik serta mengalami peningkatan hasil belajar dari nilai rata-rata kelas perlakuan dari 55 menjadi 86. Berdasarkan analisis korelasi t-tes tingkat signifikansi pengaruh pada level t-hitung 2,572 dan p-value 0,006. Pada analisis komparasi t-test tingkat signifikansinya berada pada level t-hitung bahwa t-hitung 3,563>t-tabel 2,052 dan p-value 0,001<p-tabel 0,001 dan berada pada derajat alpha 0,05. Pada tingkat efektifitas berdasar analisis n-gain berada pada level sedang atau cukup efektif pada taraf 0,57. Abstract The quality of education is closely related to the quality of learn, the use of learning resources in the surrounding environment has great benefits, especially in growing students learning experiences so that learning outcomes will improve. But students are have difficulty to learn in science subjects, one of the causes is a conventional teaching patterns, so it takes explorative and interesting learning models, such as mind mapping. Using experimental approaches in the experimental class is used mind mapping and conventional models to control class. Data collection techniques are used to measure the level of learning outcomes and observation the application of mind mapping process. The result of learning according to the learning procedure, the results of learning observation are 10 or 36% of students in the very well criteria, 11 or 39% in well criteria, 7 or 25% in quite good criteria, and none of the criteria is not good. While on the assignment observation there were 8 or 29% of students in very good criteria, 13 or 46% of students in good criteria, 7 or 25% of students in good enough criteria, and experienced an increase in learning outcomes from the average value of the experimental class from 55 to 86. Based on the t-test analysis the significance level of influence at the t-test level is 2,572 and the p-value is 0,006. In the comparative analysis t-test, the significance level is at the t-count level that the t-count is 3,563 > from the t-table 2,052 and the p-value is 0,001 < p-table 0,001 and is at the alpha degree 0,05. In the effective level based on the n-gain analysis is at the moderate level or quite effective at the level of 0,57. Keywords : Google classroom, improving learning outcomes, mind mapping